INVESTIGATION OF SUCCESSION AND TRANSFER TAX IN TERMS OF PROGRESSION IN TURKISH TAX SYSTEM - AYDIN, Murat (PEARSON JOURNAL, 2020)
Progressive tax is one of the tariffs, applied in Turkish Tax System. Progression is one of the methods used to reach the power of payment in taxation too. The progressive tax tariff in the Turkish tax system is associated with the income tax. However, succession and inheritance tax has an progressive structure in our tax system.. When the literature is examined, it is seen that the number of studies on this subject is not at the desired level. The aim of this study is to reveal the succession and inheritance tax and to examine the progressive structure. Document review technique has been used in the study. In this context, succession and inheritance tax numbered 7338 and the succession and inheritance tax law general communiqué numbered 50 have been examined in detail. At the end of the study, in succession and inheritance tax; subject, exemption, exception, taxpayer, tax return and tax base have been stated in general. In addition, the tariff structure applied in succession and inheritance tax is presented as a table and the changes of the base slice amounts according to years have been discussed.